Effectiveness of cooperative grouping in developing reading skills of university level EFL learners - Jagoda Topalov (National Research University Higher School of Economics, 2023)
Background. Collaborative Strategic Reading (CSR) is an instructional method in which students work together in a cooperative framework, jointly construct a model of text and come to its potential meaning through discussions. Purpose. A quasi-experimental pretest-posttest non-equivalent control group research design was used to examine the effects of cooperative grouping within the framework of CSR, with the aim of determining whether cooperative grouping is effective in developing EFL students' reading skills. Method. The response variables included the students' scores on questions testing Vocabulary, Factual Information, Prose Summary, Sentence Simplification, Reference Question and Insert text, whereas the explanatory variable was group membership (+/- cooperative), measured across three testing times (the beginning, middle and the end of the experimental intervention). Results. The results indicate that the students exposed to CSR within cooperative groups significantly developed those reading skills which focus on the comprehension of global information - prose summary, insert text and reference question. A possible explanation is that, in order to answer these questions, readers must approach the text in a holistic manner and focus on its main ideas, which seems to be facilitated by discussions in heterogeneous teams and negotiations of meaning resulting from those discussions. Conclusion. The main pedagogical implication of the results concerns the need for introducing cooperative grouping as an alternative to a typical university-level foreign language classroom, allowing teachers to organize an effective, interactive context for reading academic texts in English.